(untitled) (Bangladesh Journal of Medical Science, 2014)
Obligatory myiasis is invasion of vertebrate live tissue by fly larvae. This is a case report of genital myiasis caused by Wohlfahrtia magnifica in a sheep from Ghazaan village, near Ghamsar, in south of Kashan town, Iran. A sheep separated from its flock during grazing because of anorexia. Physical exam revealed genital myiasis in animal. Larvaes of fly had caused a deep wound in genital organ of this sheep. All the larvaes were removed from wound and transported to Entomology laboratory of Environmental Health Group, Kashan Medical Sciences University. Laboratory tests determined that larvaes belongs to Wohlfahrtia magnifica species. This is the first report of genital myiasis of sheep in Iran. After removing larvaes, the wound was washed with Betadine a few times, and topical antibiotics were administrated. The wound improved after a few days. The collected larvaes were cultivated in a culture medi-um with fresh meat, reached their maturity, and transformed to pupa. Pupa amounted in laboratory temperature after 5 days. Adult fly was mounted on a stereomicroscope and diagnosed as Wohlfahrtia magnifica. DOI: http://dx.doi.org/10.3329/bjms.v13i3.15451 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.332-335